Tooth Profile Modification Method of RV Reducer Cycloid Gear Aiming at Optimizing Carrying Capacity - Zongwen An; Panlong Jia; Qiang Wang; Zhili Li; Mingyuan Lei (Jixie chuandong)
Cycloid gear tooth profile modification is very important to the performance of RV reducer，in order to select the shape modification method and parameter size reasonably and improve the stress state of the cycloid tooth surface，an equidistant & radical-moving modification method based on particle swarm optimization algorithm to optimize bearing capacity is proposed. Based on the RV-60E reducer as an optimization example，the mechanical analysis of the cycloid needle wheel transmission part is carried out first，and the mathematical model of the cycloid wheel shape is established with the goal of reducing the maximum bearing capacity of the needle teeth. The required shape modification parameter values and tooth profile curve are obtained by using the proposed optimization design method. Compared with equidistant trimming，radical-moving and angle fitting modification methods，it is found that the maximum contact force of cycloidal gear profile modification method based on particle swarm optimization algorithm is reduced by 15.9%，16.0% and 11.8%，respectively，thus improving the bearing capacity and life of RV reducer.